Labour Migration from Lesotho to South Africa: Changing Patterns and Policy Implications - Motelle, Sephooko I. (Prabandhan: Indian Journal of Management, 2012)
This article attempted to analyse the changing patterns of the Lesotho-SA labour migration and adduce its policy implications. Many factors emerge to have influenced migration from Lesotho largely by males who sought work at the mines in SA; namely persistent droughts, gun fever, wars and protectionist policies embraced by SA. The decline observed in the trend of migrant mine workers in recent years, as a result of increasing retrenchments from the mines, threatens the remittances which have been a major source of household income. This delinks many families from the labour markets as many more get unemployed and would likely worsen poverty in Lesotho. This presents an enormous policy challenge for the authorities in Lesotho to look for alternative employment opportunities. Investment in education and entrepreneurial activities are suggested in this article as long-term solution to the skills constraint, and a short-term solution to absorb post-schooling-age population, respectively.